JURIDICAL ANALYSIS OF THE IMPLEMENTATION OF TICKET FINE SANCTIONS IN ELECTRONIC TRAFFIC LAW ENFORCEMENT (E-TLE) AGAINST TRAFFIC VIOLators ACCORDING TO THE LAW LAW NUMBER 22 OF 2009 CONCERNING TRAFFIC AND ROAD TRANSPORT (IN THE JURISDICTION REGIONAL POLICE OF NORTH SUMATRA) - Rosy, Deuis Rina (Inspiring Law Journal, 2024)
Electronic Trafficking Law Enforcement (ETLE) is an electronic system for monitoring traffic law enforcement which takes the form of ETLE Implementation itself, generally designed with the provisions of Law Number 22 of 2009 regarding Lailu Liintais and Aingkutain Jailain, including other enforcement agencies ETLE reaches the limit with this goal but still no success effective. Maikai dairii is necessary to research regarding the maisailaihain. This thesis is entitled "Ainailiisiis Yuriidiis Pelaiksainaiain Sainksii Dendai Tiilaing paidai Electronic Traiffiic Laiw Enforcement (ETLE) terhaidaip Pelainggaair Lailu Liintais According to Undaing-Undaing Number 22 Taihun 2009 regarding Lailu Liintais dain Aingkutain Jailain (in the Law of Diitlaintais Poldai Sumai terai Utairai)”. The method used in writing this thesis is the empiric jurisprudence research method, namely the method that focuses on the working of the laws of Maisyairaikait. The writing of this research was obtained from the source of the study, namely the study of research using the online questionnaire method which was given to the public and supported by regulations and legal matters relating to the writing of this research. The ainailiisai daitai method which is used in the ainailiais method which is obtained from the haisiil waiwaincairai using the Diitlaintais Poldai Sumaiterai Utairai method. The results of the research found that the results of ETLE's achievements to this extent have not yet been effective in terms of the results of the implementation, both internal and external, some of the results that have occurred, namely sairainai and praisairainai factors, government factors aihaimain source daiyai mainusiiai dailaim hail inii piihaik poliisiiain, faiktor cuaicai dain faiktor maisyairaikait. These haimbaitains are limited because the government has not yet achieved synergy and governmental powers, and the police have not yet achieved success. Apart from that, there are other solutions that can be differentiated into other non-compliance solutions